Family history of hypertension is associated with exaggerated cardiovascular reactivity to mental, but not to physical test (Faculty of Medicine Universitas Indonesia, 2010)
Aim To investigate whether normotensive young adults with family history of hypertension demonstrate exaggerated cardiovascular responses to both mental and physical stimuli as compared to normotensive young adults withoutfamily history of hypertension. Methods Normotensive undergraduate students of normotensive parents (n = 40) and of hypertensive father/ mother/ both (n = 40), aged 20 - 30 years, performed serial subtraction test in a sitting position for three minutes. After taking a rest, subjects performed cold pressor test in ninety seconds. In each test, blood pressure and pulse rate were recorded in pre-test, during test, and post-test using an automated oscillometric device. Changes score rather than absolute scores were analyzed using independent t-test or Mann-Whitney. Results There were no significantly differences in age, body mass index, fasting blood sugar, and plasma creatinine between the two groups. Normotensives of hypertensive parents had significantly higher offi ce systolic blood pressure (108.33 ± 1.6 vs 103.00 ± 1.6 mmHg) and delta change score of cardiovascular reactivity to serial subtraction test (MABP 19.13 ± 1.4 vs 15.5 ± 1.0 mmHg, P = 0.04), but not to cold pressor test (MABP 24.26 ± 1.7 vs 21.74 ± 1.7 mmHg) than those of normotensive parents. Conclusion Normotensive young adults with family history of hypertension demonstrated exaggerated cardiovascular reactivity to mental test but not to physical test. As compared to normotensive young adults without family history of hypertension However, this familial difference in cardiovascular reactivity to mental test is confused with office blood pressure. (Med J Indones 2010; 19:118-23)